2020
DOI: 10.18388/abp.2020_5413
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro activity of lipoic acid against Ureaplasma urealyticum and Ureaplasma parvum isolated from women with infections of the urogenital tract. A pilot study

Abstract: Several species of Ureaplasma bacteria are known to be present in the urogenital tract of humans, in both healthy individuals and symptomatic patients. These pathogens are associated with urogenital tract infections, infertility problems and spontaneous abortion in humans. The present study involved 77 strains of Ureaplasma species (Ureaplasma spp.), including 21 Ureaplasma urealyticum (U. urealyticum) strains and 56 Ureaplasma parvum (U. parvum) strains. Lipoic acid (LA) and its reduced form dihydrolipoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In our previous research on Ureaplasma urealyticum and Ureaplasma parvum , we observed that LA only at a concentration of 1,200 μg/ml had a statistically significant ( p < 0.001) inhibitory effect on cell division of Ureaplasma strains compared to the control ( Biernat-Sudolska et al 2020 ).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…In our previous research on Ureaplasma urealyticum and Ureaplasma parvum , we observed that LA only at a concentration of 1,200 μg/ml had a statistically significant ( p < 0.001) inhibitory effect on cell division of Ureaplasma strains compared to the control ( Biernat-Sudolska et al 2020 ).…”
Section: Resultsmentioning
confidence: 82%
“…The studies on the LA effect on bacteria multiplication and its bactericidal activity against these cells have not yet been published. The only paper that showed the antimicrobial activity of LA on bacterial cells belonging to the family Mycoplasmataceae (these were strains of Ureaplasma urealyticum and Ureaplasma parvum ) was published by Biernat-Sudolska et al (2020) .…”
Section: Introductionmentioning
confidence: 99%
“…The applied therapy eliminated the need for liver transplantation [ 123 ]. The antibacterial effect of LA has not been so clearly demonstrated, however, there are several studies showing its effectiveness in this area [ 124 , 125 ].…”
Section: Lipoic Acid (La) and Covid-19mentioning
confidence: 99%
“…who received antibacterial therapy initially with azithromycin and then doxycycline for 7 days, or vice versa, were still colonized with these bacteria after 6 weeks of treatment [ 6 ]. Biernat-Sudolska et al showed that as many as 90% of U. parvum strains and 83% of U. urealyticum strains present in the tracheal aspirate of premature newborns were resistant to ciprofloxacin belonging to the fluoroquinolone class [ 7 ]. Yang et al indicated that the resistance rates of levofloxacin were 82.43% for U. urealyticum and 84.69% for U. parvum , and those of moxifloxacin were 62.16% for U. urealyticum and 51.44% for U. parvum [ 8 ].…”
Section: Introductionmentioning
confidence: 99%